2021
DOI: 10.1101/2021.05.07.443092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The P2RX7B splice variant modulates osteosarcoma cell behaviour and metastatic properties

Abstract: Osteosarcoma (OS) is the most common type of primary bone cancer affecting children and adolescents. OS has a high propensity to spread, meaning the disease is often incurable and fatal. There have been no improvements in survival rates for decades. This highlights an urgent need for development of novel therapeutic strategies. In this study, we have produced in vitro and in vivo data that demonstrates the role of purinergic signalling, specifically, the B isoform of the purinergic receptor P2RX7 (herein terme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Among them, P2X7B and nfP2X7 isoforms have attracted most attention due to their inabilities to form macropore followed by cell death (22,69). The preferential expression of P2RX7B variant has also been observed in OS, which regulates OS growth and metastasis (33). Moreover, eATP induces nfP2RX7 expression and thus enhances tumor cell survival (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, P2X7B and nfP2X7 isoforms have attracted most attention due to their inabilities to form macropore followed by cell death (22,69). The preferential expression of P2RX7B variant has also been observed in OS, which regulates OS growth and metastasis (33). Moreover, eATP induces nfP2RX7 expression and thus enhances tumor cell survival (22).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to OS, various studies have also been conducted on the role of glucose metabolism in tumor progression and underlying mechanisms (30)(31)(32). Previous studies have suggested that P2RX7 is involved in biological behavior of OS cells (33,34). However, to our knowledge, whether and how P2RX7 regulates OS growth and metastasis through metabolic reprogramming remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Following dehydration, sections were mounted with EUKITT (Kindler GmbH), and images acquired thanks to NIS-elements software with a Nikon Eclipse 90i digital microscope (Nikon Instruments, Europe). The percentage of positive cells was quantified using the QuPath free software for immunohistochemical analysis (Bankhead et al, 2017) as previously described (Tattersall et al, 2021).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…This naturally occurring P2X7RB isoform maintains ATP-stimulated channel activity but not pore permeabilization [2, 3]. P2X7RB is upregulated in epithelial cancer cells [3] and associated with the trophic activity of primary bone cancer [2,4,5]. These findings have highlighted the importance of defining the role of P2X7R C-terminal truncated variants in cancer progression, particularly considering that data on…”
mentioning
confidence: 99%